An Analysis of Heisenberg's Uncertainty Principle in Mark Z. Danielewski's House of Leaves - Abasy, Mahdiye; Sadati, Seyyed Shahabeddin (LANGUAGE ART, 2023)
This study is an analysis of Heisenberg's uncertainty principle in Mark Z. Danielewski's House of Leaves. According to Heisenberg, the position and velocity of a particle cannot be measured simultaneously, and an electron exists in an indefinite state. From the uncertainty principle perspective, this study aims to analyze how postmodern techniques cause uncertainty and make readers experience superposition, ambivalent feelings, and indefinite states. As a result of the uncertainty principle, the quantum parallel worlds appear in each part of the novel to a reader's mind. Both post-structuralism and quantum physics rejected reality; however, what mattered was the reader's role (or the observer's role) in deciding to create a single reality. From the frog viewpoint, there was only the reader's reality in parallel worlds, whereas multiple realities emerged from the bird viewpoint. These two viewpoints should not be ignored while analyzing the ontology of House of Leaves. Therefore, it can be proved that there is a close relationship between postmodern literature and physics. In the 20th century, scientific discoveries have affected literature. Like any other postmodern works, House of Leaves was inspired by quantum physics.